The Middle Assyrian Laws - Saporetti, С. (1984)
System design and introduction: G. Buccellati; programming: J. L. Settles - D. A. Holzgang - I.R.Paul; data entry: С. Saporetti - M. Sassi - A. Ghiroldi; data coordination: M. L. Jaffe.